Resilient Coping Moderates the Effect of Trauma Exposure on Depression. Issue 4 (13th May 2016) - Sinclair, Vaughn G.; Wallston, Kenneth A.; Strachan, Eric
Abstract: Posttraumatic depression rates are increasing in the United States, and there is a great need to identify malleable factors that could moderate posttraumatic depression levels. The purpose of this study was to examine whether resilient coping moderates the effects of trauma exposure on depression, while controlling for neuroticism—an established predictor of depressive symptoms. This study used data from 3, 734 pairs of twins from the community‐based University of Washington Twin Registry. Each twin pair was randomized with twin A in one subsample and twin B in the second subsample. The four‐item Brief Resilient Coping Scale measured resilient coping. The two‐item Patient Health Questionnaire measured depression. Multiple linear regression analyses were performed on each subsample, controlling for neuroticism. In addition to significant effects of neuroticism and trauma exposure on depression ( p  < .001), the effect of the interaction of resilient coping and trauma exposure on depression was significant in both subsamples ( p  < .01). High levels of resilient coping were associated with lower depression scores in the context of previous trauma exposure. Individuals high in resilient coping who experienced significant life traumas were less depressed after trauma exposure, even after controlling for neuroticism. Because coping skills may be learned, interventions that teach resilient coping to individuals with traumatic histories merit investigation. © 2016 Wiley Periodicals, Inc.